Prevelance of hepatitis D co-enfection in children with hepatitis B infection: Cross-sectional analyses from Western Turkey - Funda ÖZGENÇ,; Çiğdem ÖMÜR ECEVİT,; Gülin ERDEMİR,; Rüçhan SERTÖZ,; Raşit Vural YAĞCI, (Turkish Journal of Gastroenterology, 2019)
-